Women and power transformation in rural households in Saki West Local Government Area of Oyo state (2013)
Rural women contribute significantly to the national economy by their activities in terms of agricultural production, marketing, processing and domestic work. It is ironical that their contribution either have no or minimal part in the decision making power regarding agricultural development and household activities. The study presents the past and current trends in household power sharing in Saki West Local Government Area of Oyo state, Nigeria. Data were collected using structured questionnaires from 140 respondents. Results show that majority of the respondents (69.4%) were within the ages of 35-42years, 45% were illiterates, 51.5% were 15-20years in marriage, while 90.8% had 3-8 household size. The current trend is that women are making decisions on their land, children, when to have sex, and type of family planning to use. Women will be able to have more power with her level of education (p=0.035). Number of wives (p=0.123) and children (p=0.316) had no effect on power transformation. Changes are occurring in women's economics status since they are in control of their finances and these are impacting their decision making power within household. Women should be empowered educationally and be more enlightened on the need for reduction in child bearing in order to reduce poverty rate.